Aspectos teóricos de la organización y funcionalidad de bandos nobiliarios en Castilla (siglo XV) (Estudios de Historia de España, 2016)
This study is about the specific characteristic of noble factions in Castillan´s policy during the XVth. century. We started from two questions: the first about the functionality of noble factions for the kings and the second, about the meaning that fights between noble factions had for monarchy as institution. At last we looked for a political thought that linked actions with theories about policy. In spite of the research we could not find a political thought but strategies with few background in doctrinal theories.
Keywords: Noble factions; Function; Institution; Organization; Strategy; Policy; Political thought